Development of a specific molecular tool for detecting Xanthomonas campestris pv. musacearum - Adikini, S.; Tripathi, L.; Beed, Fenton D.; Tusiime, Geoffrey; Magembe, E.M.; Kim, D.J. (Wiley, 2011)
A specific and rapid diagnostic tool has been developed to detect Xanthomonas campestris pv. musacearum, the causal agent of bacterial wilt of banana. PCR primers were developed from intergenic regions of X. campestris pv. musacearum following its partial sequence. A total of 48 primers were tested for specificity to X. campestris pv. musacearum strains collected from various regions in Uganda. These were also tested for specificity against related Xanthomonas species from the vasicola group, Xanthomonas species pathogenic to other crops, and against those existing saprophytically on banana plants. Seven primer sets (Xcm12, Xcm35, Xcm36, Xcm38, Xcm44, Xcm47 and Xcm48) were found to be very specific to X. campestris pv. musacearum. These primer sets directed the amplification of the expected product for all 52 strains of X. campestris pv. musacearum collected from different locations in Uganda. No amplification products were obtained with unrelated phytopathogenic bacteria or endophytic ⁄ epiphytic bacteria from banana. A detection limit of 103 CFU mL)1 corresponding to about four cells per PCR reaction was observed when X. campestris pv. musacearum cells were used for all the seven primer sets. The DNA samples from symptomless plant tissues also tested positive with primer set Xcm38. The specific PCR method described here is a valuable diagnostic tool which can be used to detect the pathogen at early stages of infection and monitor disease.